Lebak Regional Government's Strategy in Facing Cultural Resistance In Baduy Indigenous Community - Lindyana Sartika Soraya; Isbandi Rukminto Adi (Cita Konsultindo Research Center, 2024)
The development of Indigenous Ecotourism carried out by the government in the Baduy Traditional Village often raises resistance and friction because it is considered to be contrary to the rules and the customary behaviour that applies in the Baduy indigenous community that has been passed down from generation to generation. The purpose of this writing is to discuss the government's strategy in dealing with cultural resistance that occurs in the Baduy Customary Tourism Village related to the implementation practices by the Lebak regional government in developing indigenous ecotourism with the expectations of the community by the prevailing customary order and seeing the efforts that the Lebak Regency government has made in easing cultural resistance in the development of the Baduy Customary Tourism Village. By using a qualitative approach with a descriptive type of research, the researcher conducts research including observation techniques, interviews, and literature studies and uses supporting instruments for this research are interview guidelines, sound recording devices and cameras; this study emphasizes a detailed examination of the various resistances that occur in the Indigenous Baduy community that arise against the development of Indigenous Ecotourism carried out by the government naturally in social life and adjusts to the efforts that have been made. Subscribe to DeepL Pro to edit this document. Visit www.DeepL.com/pro for more information. This study concludes that the government's identification and points of strategies in reducing resistance are to the reality that occurs in the field. The conclusion of this study is the identification and issues of strategies carried out by the government in easing resistance in indigenous communities with the development of Indigenous Ecotourism in the Baduy Customary Tourism Village and emphasizing the results of the formulation of alternative conflict solutions between customs and the government through in-depth studies of both.